Development of Teak Wood Powder–Epoxy Composite for Motorcycle CVT Weight Rollers Application - R. Dwi Pudji Susilo; Muhamad Fitri; Muhammad Sulthan Yafiq; Abdul Hamid; Dedik Romahadi (Universitas Mercu Buana, 2026)
The development of sustainable materials for automotive components has become increasingly important due to environmental concerns associated with conventional synthetic materials. This study investigates the feasibility of teak wood powder (Tectona grandis L.F.) reinforced epoxy composites as an eco-friendly alternative to polytetrafluoroethylene (PTFE) for Continuously Variable Transmission (CVT) weight rollers. The composite was fabricated using a hot-press method with varying composition ratios (60:40, 70:30, and 80:20) and processing temperatures (160 °C, 170 °C, and 180 °C) under a constant pressure of 20 bar. Mechanical performance was evaluated through tensile testing in accordance with ASTM D3039. The results demonstrate that both composition and processing temperature significantly influence tensile strength. The optimal condition—60% teak wood powder and 40% epoxy resin processed at 180 °C—yielded the highest average tensile strength of approximately 25 MPa, surpassing the typical value of conventional PTFE-based rollers ( 23 MPa). The improvement is attributed to enhanced matrix–filler bonding and better resin flow at elevated temperatures, resulting in more effective load transfer and reduced void formation. Conversely, higher filler content led to reduced performance due to insufficient matrix continuity and increased interfacial defects. This study provides a significant contribution by demonstrating that teak wood waste can be effectively utilized as a reinforcement material in structural automotive applications. The findings highlight a viable pathway toward cost-effective, sustainable composite design while maintaining competitive mechanical performance. Further investigation on tribological behavior and long-term durability is recommended to support real-world implementation.